Pembelajaran Berbasis Proyek (Project Based Learning) Materi Kalor dan Perpindahannya untuk Meningkatkan Kreativitas Siswa - Diah Nugraheni (Universitas PGRI Semarang, 2018)
This research aims to train students in designing projects to create products related to the concept of heat dan transfer material. This research is a classroom action research conducted systematically as an effort to improve the implementation of learning by doing innovative actions in the learning process using project based learning model. The results show that project based learning on heat and transfer material makes students trained in project design and making products related to heat and transfer. Student responses to project based learning developed have good categories, so it can be said to be effective to apply in learning.Keywords: project based learning, heat and transfer, creativity.